Parenting Communication Education and Adolescents’ Preventive Intentions Toward Early Marriage: A Quasi-Experimental Family-Centered Intervention Study - Elfina Elfina; Fadly Umar; Dewi Lestari; Dhea Karolina; Magfirah Magfirah (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Early marriage remains a significant public health concern because it is closely associated with adolescent pregnancy, limited educational attainment, and increased risk of maternal and child health problems, including stunting. Family dynamics and parent–adolescent communication play an important role in shaping adolescents’ knowledge, attitudes, and preventive intentions regarding marriage timing and reproductive health. This study aimed to examine the short-term effect of parenting communication education as a family-based intervention to improve knowledge, attitudes, and behavioral intentions related to early marriage prevention in a community setting. Methods: This study employed a quasi-experimental design with a pre-test–post-test control group structure. A total of 60 respondents were divided into an intervention group and a control group, each consisting of 30 participants. Participants were adolescents aged 15–18 years and parents from the working area of Biromaru Community Health Center and SMK 1 Sigi, selected according to predefined eligibility criteria. The intervention group received parenting communication education focusing on parent–adolescent dialogue, reproductive health awareness, and the risks associated with early marriage, while the control group did not receive the intervention during the study period. Data were collected using structured questionnaires that had undergone validity and reliability testing to measure knowledge, attitudes, and behavioral intentions related to early marriage prevention. Statistical analysis was conducted using paired t-tests to assess within-group changes and independent t-tests to compare outcomes between groups, with findings interpreted as short-term psychosocial changes rather than verified behavioral outcomes. Result: The results demonstrated significant improvements in the intervention group across all measured domains. Knowledge scores increased from 55.6 ± 8.2 to 82.4 ± 5.7 (p < 0.001), indicating enhanced understanding of reproductive health risks and the consequences of early marriage. Attitude scores also improved from 60.3 ± 9.1 to 84.1 ± 7.4 (p < 0.001), reflecting stronger rejection of early marriage and greater awareness of the importance of mental and social preparedness for parenthood. Behavioral intention scores showed the largest improvement, increasing from 50.2 ± 8.1 to 88.1 ± 6.9 (p < 0.001), suggesting stronger intention to delay marriage and prioritize education and reproductive health preparation. In contrast, the control group showed only limited changes across the measured domains. These findings suggest that family-based educational interventions may strengthen parent–adolescent communication and reinforce normative support for delaying marriage, although longer-term follow-up is required to determine whether these intentions translate into actual behavioral outcomes. Conclusion: In conclusion, parenting communication education represents a promising strategy for preventing early marriage by strengthening family communication, improving reproductive health knowledge, and promoting preventive attitudes and behavioral intentions. Integrating family-based education into adolescent health programs may support upstream prevention pathways associated with early marriage and stunting risk, but its effects on actual marriage timing, reproductive health behavior, and child nutritional outcomes require longitudinal verification.